The microfluidic nebulator: production of sub-micrometer sized airborne drops. Issue 8 (15th March 2017) - Amstad, Esther; Spaepen, Frans; Brenner, Michael P.; Weitz, David A.
Abstract : Many powders employed in the food and pharmaceutical industries are produced through spray drying because it is a cost efficient process that offers control over the particle size. Abstract : Many powders employed in the food and pharmaceutical industries are produced through spray drying because it is a cost efficient process that offers control over the particle size. However, most commercially available spray-driers cannot produce drops with diameters below 1 μm, limiting the size of spray-dried particles to values above 300 nm. We recently developed a microfluidic spray-drier that can form much smaller drops than commercially available spray-driers. This is achieved through a two-step process: first, the microfluidic spray-drier operates in the dripping regime to form 100 μm diameter primary drops in air and, second, subjects them to high shear stresses due to supersonic flow of air to break them into many much smaller secondary drops. In this paper, we describe the two essential steps required to form sub-μm diameter airborne drops inside microfluidic channels. We investigate the influence of the device geometry on the ability to operate the microfluidic spray-drier in the dripping regime. Moreover, we describe how these primary drops are nebulized into many secondary drops that are much smaller than the smallest dimension of the spray-drier channels.